Depressive symptoms screening in postmenopausal women with symptomatic pelvic organ prolapse. Issue 3 (March 2018) - Ai, Fangfang; Deng, Mou; Mao, Meng; Xu, Tao; Zhu, Lan
Abstract: Objective: This study aimed to investigate the prevalence of depressive symptoms in postmenopausal women with symptomatic pelvic organ prolapse (POP) and to identify the factors associated with depressive symptoms in this population. Methods: We conducted a cross-sectional study involving postmenopausal women with symptomatic POP who visited the Center of Obstetrics and Gynecology, Peking Union Medical College Hospital, Beijing, between July 2016 and March 2017. We collected data pertaining to participants' sociodemographic characteristics and medical histories. The participants enrolled in the study were evaluated by POP quantification (POP-Q), the Pelvic Floor Distress Inventory-20 (PFDI-20), and the Pelvic Floor Impact Questionnaire-7 (PFIQ-7), and the severity of their depressive symptoms was assessed by the Patient Health Questionnaire-9 (participants with scores ≥10 were considered "positive" for depressive symptoms, whereas participants with scores <10 were considered "negative" for depressive symptoms). We performed independent-sample t tests, Mann-Whitney U test, chi-square tests, Fisher's exact test, and logistic regression to analyze our data. Results: In all, 177 participants completed the entire study and were thus included in the analysis. Overall, 32.8% of participants were found to have depressive symptoms. We noted no differences in sociodemographic characteristics or POP-Q stage between participants with and without depressive symptoms ( P > 0.05). However, depressive symptoms were associated with higher PFIQ-7 and PFDI-20 subscale scores ( P < 0.001). PFIQ-7 subscale Urinary Impact Questionnaire (UIQ)-7 (odds ratio [OR] 1.038, 95% confidence interval [CI] 1.010-1.066, P = 0.008), PFDI-20 subscale UDI-6 (OR 1.025, 95% CI 1.007-1.044, P = 0.008), and Colorectal-Anal Distress Inventory-8 (OR 1.025, 95% CI 1.005-1.046, P = 0.016), which represented the impact on quality of life from lower urinary tract symptoms, the distress caused by lower urinary tract symptom and bowel dysfunction, respectively, were the risk factors that were independently associated with depressive symptoms after multiple logistic regression analysis. Conclusions: Depressive symptoms were present in approximately one-third of postmenopausal women with symptomatic POP. Depressive symptoms are not associated with POP stage, but are associated with the lower urinary tract symptom and bowel dysfunction scores attributable to prolapse. Clinicians should be mindful of whether patients with symptomatic POP have depressive symptoms and should address POP and any concomitant depressive symptoms as early as possible.